2014
DOI: 10.1177/1076029613518368
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio is Predictor of Atrial Fibrillation Recurrence After Cardioversion With Amiodarone

Abstract: Increased NLR is a marker of increased inflammation and may serve as simple, cheap, and readily available predictors of recurrence in the long-term follow-up of patients admitted with acute AF and successfully converted to SR with amiodarone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
0
19
0
2
Order By: Relevance
“…The NLR in the peripheral blood is known to be a rapid indicator of physiologic stress, and this value may be an independent predictor of recurrence in patients with atrial fibrillation and various cancers [11][12][13]. Compared to the values in the control group, there was an increase in NLR and PLR values in both episodes, after adjustments for sex and age, respectively (p < 0.001).…”
Section: Discussionmentioning
confidence: 91%
“…The NLR in the peripheral blood is known to be a rapid indicator of physiologic stress, and this value may be an independent predictor of recurrence in patients with atrial fibrillation and various cancers [11][12][13]. Compared to the values in the control group, there was an increase in NLR and PLR values in both episodes, after adjustments for sex and age, respectively (p < 0.001).…”
Section: Discussionmentioning
confidence: 91%
“…Patients with nonvalvular AF have increased NLR with further 36% rise in NLR values from those with paroxysmal form of the arrhythmia to those with persistent/permanent AF . Increased NLR has also been independently associated with AF recurrence after cardioversion with amiodarone, as well as AF recurrence after ablation procedures . Conflicting results have been reported for postoperative AF in patients undergoing nonemergency coronary artery bypass surgery, although one large study supported NLR‐related risks of AF occurrence.…”
mentioning
confidence: 99%
“…A few studies have recently reported the relationship between the neutrophil to lymphocyte ratio (NLR) and AF. 7) 8) 9) 10) 11) 12) The NLR has emerged as a novel systemic inflammatory marker and a prognostic indicator of cardiovascular disease. 7) 8) The potential association between the NLR and development of AF has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“… 7) 8) The potential association between the NLR and development of AF has also been reported. 9) 10) 11) 12) …”
Section: Introductionmentioning
confidence: 99%